2012
DOI: 10.1111/j.1475-1313.2012.00912.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral refraction in myopia corrected with spectacles versus contact lenses

Abstract: Correcting the on-axis refractive error in moderate to high myopia with conventional spherical spectacle lenses results in hyperopic defocus in the peripheral retina. Correcting the same eyes with conventional spherical soft contact lenses results in significant myopic defocus in the peripheral retina. These results corroborate the general findings of earlier studies and the predictions of optical modelling by others. If the refractive status of the peripheral retina does influence myopia progression, then the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 39 publications
3
39
0
2
Order By: Relevance
“…Peripheral myopic shifts have been reported with Acuvue 1-Day Moist, Acuvue2, and Air Optix Night & Day Aqua contact lenses. 16, 4749 A hyperopic shift in peripheral defocus has been reported with Proclear and Acuvue2 contact lenses. 49, 50 Although a previous study of Biofinity reported no significant differences in peripheral defocus caused by the lens at most retinal locations, a sudden myopic shift in peripheral defocus at 40 degrees temporal on the retina was reported similar to the profile found in this study.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Peripheral myopic shifts have been reported with Acuvue 1-Day Moist, Acuvue2, and Air Optix Night & Day Aqua contact lenses. 16, 4749 A hyperopic shift in peripheral defocus has been reported with Proclear and Acuvue2 contact lenses. 49, 50 Although a previous study of Biofinity reported no significant differences in peripheral defocus caused by the lens at most retinal locations, a sudden myopic shift in peripheral defocus at 40 degrees temporal on the retina was reported similar to the profile found in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Several previous studies had smaller sample sizes of between 10 to 11 subjects, 16, 47, 48 only evaluated one soft contact lens design, 16, 47, 48, 50 or did not measure as far into the periphery with maximum measurement locations of 20 degrees, 47 30 degrees, 16, 48 and 35 degrees 50 from the line of sight. While most studies have used open-field autorefraction to measure defocus, Shen at al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Wear of conventional spectacles does appear to contribute to this peripheral defocus, 27,28 which provided the impetus for the randomized trials of under-correction in preventing myopia progression as cited above. 14,15 The mechanism whereby spectacle wear (compared to nonwear) appears in fact to retard worsening of vision associated with progression of myopia is not well understood.…”
Section: Results From Itt Analysis In This Randomized Trialmentioning
confidence: 99%
“…Furthermore, experimental evidence supports the notion that visual stimulus detection and signaling from the retina to the sclera occur locally [35–38; 91]. In particular, peripheral defocus is thought to promote myopia in humans [9297]. We imposed heterogeneous scleral remodeling across the scleral shell using the function δ α .…”
Section: Discussionmentioning
confidence: 99%